Optimization of glucose production from rice husk by using cellulase enzyme - Nurhidayah Kamaruddin (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Rice husk is lignocellulosic substrates which are the agricultural wastes and by-products of rice hulling plants available in large amount of quantity, cheap and are used to produce glucose. Production of glucose from agro-waste is one way to reduce the abundance of waste on the plantation floor. Enzymatic hydrolysis is one of the easiest ways which help in converting the lignocellulosic materials into functional product that is glucose